Characteristics of the Tapanuli Orangutan Habitat in the Conflict Area of Batang Toru Landscape, North Sumatra, Indonesia - Kuswanda, Wanda; Harahap, R. Hamdani; Alikodra, Hadi S.; Sibarani, Robert (Forest and Society, 2021)
Forest fragmentation has resulted in decreased wildlife habitat, which has triggered conflicts with humans due to the use of the same plants. This has been particularly contentious with the tapanuli orangutan. Research of the tapanuli orangutan (Pongo tapanuliensis) habitat is very limited. The aims of this research is to examine the latest habitat conditions, such as land cover, composition of vegetation, feed plant, and habitat carrying capacity to provide recommendations for habitat management in developing a mitigation policy of the human-tapanuli orangutan conflict. The research location is focused on the area of human-orangutan conflict in the Batang Toru Landscape in South Tapanuli Regency, which took place from August to December 2019. Vegetation analysis was conducted using the strip transect method with a total of 294 plots (11.76 ha). The number of species at the pole and tree levels were high with 149 species (46 families) and diversity index (H') > 3. Eighty feed plant species were found and expected to support the growth of the orangutan population of 247 individuals. The density and diversity of cultivated plant species in the buffer zone were high and consumption by orangutans resulted in human-tapanuli orangutan conflict, especially on durian (Durio zibethinus Murray). Conflict with humans will cause stress and disruption to the growth of the tapanuli orangutan. We recommend habitat management to mitigate conflict through patrols for monitoring habitat destruction in conservation forests, enrichment of feed plants in Forest Management Units, cultivation of orangutan non-food crops on community lands, and building a corridor with orangutan food crops with fruits that are not utilized by humans.